Reconstruction as an Opportunity to Reduce Risk? Physical Changes Post-Wildfire in Chilean Case Studies - GONZALEZ MATHIESEN, MARIA CONSTANZA; Natalia Aravena-Solís; Catalina Rosales (MDPI AG, 2025)
Post-wildfire reconstruction processes offer an opportunity to implement structural risk reduction measures and develop wildfire resilience; however, these efforts often lack comprehensiveness. Focusing on Chile, this research addresses the need for increased and nuanced understanding of the implementation and subsequent modifications in wildfire risk reduction actions in the built environment during post-wildfire reconstruction processes. Accordingly, this study aims to identify the physical changes associated with implementing structural wildfire risk reduction measures in Chile’s reconstruction efforts from their establishment to the present, organized based on two secondary objectives: (1) document the physical changes that have occurred following the disaster, and (2) distinguish and categorize the reconstruction interventions. A mixed-methods multiple case study approach was employed, analyzing four post-wildfire reconstruction processes (Valparaiso, 2014; Santa Olga, 2017; Castro, 2021; and Punta Lavapie, 2023) through spatial analysis of physical changes and qualitative content analysis of documents to identify and categorize interventions. The research found that structural wildfire risk reduction measures and wider settlement improvements have been implemented in all case studies with varying emphasis and comprehensiveness. However, the results also suggest that these reconstruction efforts have not improved settlements’ long-term wildfire resilience. This study contributes to the theory and practice of reconstruction and risk reduction by showing that the post-disaster period often fails to lead to lasting systemic change.